Electronic band structure of Ge1-xSnx alloys - Yu, Cunyang (2018)
Semiconductor alloys have been widely used in engineering and the different material properties can be obtained by changing the composition of the alloy. Ge and Si are extensively used in electronic devices. However, the indirect nature of the band gap of group IV materials is the mainly limitation for the application in the optoelectronics. Ge1-xSnx is a promising alloy to tune the nature of indirect band gap to direct bandgap by tuning the composition of Sn. This project is to investigate the electronic band structure of Ge1-xSnx in different composition of Sn and the influence of the change of other parameters such as temperature and tensile. The k.p method will be used to calculate the band edge dispersion at Γ-point.